Self-Association Study from Electrochemical Behaviours of Mo154 and Mo72Fe30 in Aqueous Solution - Jia, Xiangfeng; Yu, Shuaiqin; Ma, Yongshan; Li, Peigang; Ren, Huixue (Asian Journal of Chemistry, 2010)
The electrochemical behaviours of the nanoscale inorganic polyoxomolybdate anions (Mo154 and Mo72Fe30) and their aggregations in aqueous solution are examined by cyclic voltammetry. By comparison, it is found that the cyclic voltammograms of the single macro anions (Mo154 and Mo72Fe30) and those of their aggregations are similar. From the electrochemical point of view, it is concluded that the self-assembly of this kind of macro anions is driven by physical force.